A Preliminary Study of Jemaah Islamiyah in Indonesia and The Doctrine of Suicide Bombing - Muhaemin Latif (Universitas Islam Negeri Alauddin Makassar, 2012)
The Existence of Jemaah Islamiyah in the world, particularly in Indonesia, cannot be underestimated by the Indonesian government. It is extremely needed a serious attention to tackle this movement. This essay entails a strong network between JI in Indonesia and al-Qaedah Link in Afganistasn. Although the emergence of JI in Indonesia cannot be separated from a former rebellion to the Indonesia New Order which was called Darul Islam, the development of JI has remarkably changed through building strong networking to international link like al-Qaedah. A number of evidence has been provided in this article to strengthen the danger of this organization. The doctrine of jihad through suicide bombing fuels the threat of JI as an international terrorist organization. Jihad was believed as the holy war against the United States, Israel, Europe, and anyone else who oppose their vision of world governed by shariah. JI itself were supported by multitude schools, charitable associations, banks, business activities and Islamic world government.